2022
DOI: 10.1038/s41467-022-33778-9
|View full text |Cite
|
Sign up to set email alerts
|

Coupling photocatalytic water oxidation with reductive transformations of organic molecules

Abstract: The utilization of readily available and non-toxic water by photocatalytic water splitting is highly attractive in green chemistry. Herein we report that light-induced oxidative half-reaction of water splitting is effectively coupled with reduction of organic compounds, which provides a light-induced avenue to use water as an electron donor to enable reductive transformations of organic substances. The present strategy allows various aryl bromides to undergo smoothly the reductive coupling with Pd/g-C3N4* as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…In theory, such an electronic effect agrees with the SeT mechanism because an increase in the electron density of the aromatic ring would accelerate the SeT from the catalyst to the substrate by improving the electron-accepting capacity of the substrate. 67–69 Moreover, such an electronic effect has been authenticated in previous literature as SeT-mediated cleavage of aryl C–Br bonds. 67–69 In contrast, oxidative metal addition-mediated reactions have a different electronic effect: electron-deficient aryl halides have lower reactivity.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In theory, such an electronic effect agrees with the SeT mechanism because an increase in the electron density of the aromatic ring would accelerate the SeT from the catalyst to the substrate by improving the electron-accepting capacity of the substrate. 67–69 Moreover, such an electronic effect has been authenticated in previous literature as SeT-mediated cleavage of aryl C–Br bonds. 67–69 In contrast, oxidative metal addition-mediated reactions have a different electronic effect: electron-deficient aryl halides have lower reactivity.…”
Section: Resultsmentioning
confidence: 77%
“…67–69 Moreover, such an electronic effect has been authenticated in previous literature as SeT-mediated cleavage of aryl C–Br bonds. 67–69 In contrast, oxidative metal addition-mediated reactions have a different electronic effect: electron-deficient aryl halides have lower reactivity. 71,72 In summary, the observed electronic effect under our conditions is consistent with SeT rather than the oxidative metal addition mechanism, which confirms the reliability of our conclusion that the present reactions proceed via the SeT mechanism.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…As the most common and nonpolluting solvent, water also has enormous potential for use in other types of reactions. It has been demonstrated that water can participate in reactions as an oxidizing or reducing agent, such as hydrogenolysis and couplings. , This provides directions for the development of water involvement in reactions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that water can participate in reactions as an oxidizing or reducing agent, such as hydrogenolysis 60 and couplings. 61,62 This provides directions for the development of water involvement in reactions. In conclusion, although the field is still in its nascent stage and has many challenges, discoveries will propel the field by solving these issues with an increasing understanding of their organocatalytic and photochemical reactivity, which will have a significant impact on the energy transition to a zero-carbon economy.…”
Section: Discussionmentioning
confidence: 99%